Agri-food cooperatives integration processes. From the norm to the reality. Special reference to the Law 12/2013 to promote the cooperative integration - Meliá Martí, Elena; Peris Mendoza, Manuel (REVESCO. Revista de Estudios Cooperativos, 2018)
Spanish agri-food cooperative movement is characterized by great economic, social and geographical development. However, among its main weaknesses it can be highlighted their significant fragmentation, with many entities of very small size, which places them in a situation of vulnerability in the market.In this context, Law 13/2013, to promote associative integration, with the figure of the Priority Associative Entity (PAE), and RD 550/2014, which establishes the requirements and the procedure for its recognition, must influence the size of cooperative organizations.Faced with this reality, this paper analyzes the potential achievement of the objectives set out in the Law 13/2013 (with its current configuration), to increase the size of Spanish agri-food cooperatives, which to date has had a limited aplication (only 6 entities have obtained the PAE recognition). For that purpose, it has been prepared a survey of the 274 Spanish cooperatives with largest sections. At the same time, it analyzes if the reason for such scarce application lies in the level of difficulty in reaching the minimum requirements established in it.Through the survey, it has been studied:- The expected degree of achievement of the four objectives of the Law, paying particular attention to the increase of the size of cooperatives according to their size,- The level of difficulty to meet the requirements established to be recognized as a PAE.
Keywords: Cooperative integration; Agri-food cooperative; Priority Associative Entity; Business concentration.